Auditing the proposed greenhouse gas emissions management in accordance with the International Assurance Engagement Standard 3410 to reduce the effects of climate change: (applied research (Central Refineries Company/Al Doura Refinery (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:             The research seeks to manage greenhouse gas emissions in accordance with the International Assurance Engagement Standard 3410 and relevant international standards to reduce the effects of climate change. The problem of the research is that despite the existence of environmental laws, regulations and instructions in addition to Iraq’s accession to a number of international agreements The relevant ones, which aim to report gaseous emissions, but they are not committed to implementing them, and there are no audit procedures issued by the Federal Financial Supervision Office to audit greenhouse gas emissions and their impact on climate change. The importance of the research lies in reporting the main matters in the audit when preparing the auditor’s report that would help reduce the effects of climate change. The research was based on the hypothesis that procedures for auditing the management of greenhouse gas emissions in accordance with the international assurance engagement standard 3410 contribute to reducing the effects of climate change. In preparing the research, the two researchers relied on environmental laws, regulations, instructions, and relevant international agreements, in addition to relevant conferences. The relationship and data obtained from the Central Refineries Company / Al-Dora Refinery, the Meteorological and Seismic Monitoring Authority, as well as environmental reports, reports from the Federal Financial Supervision Bureau, and the Internet.The researchers reached a set of conclusions, the most important of which is that the relevant laws, regulations, instructions and international agreements are not adhered to, and there are no procedures for auditing greenhouse gas emissions in the Federal Audit Office. The most important recommendations that the researchers reached were the necessity of adhering to the laws and regulations. And environmental instructions and international agreements. It is also necessary to adhere to the sustainable development goals, especially Goal (13) (urgent measures to address climate change and its effects), in addition to the necessity of adopting the proposed auditing procedures for the purpose of controlling gaseous emissions and thus reducing the effects of climate change.